SISTEMAS DE EJERCICIOS EN EL DESARROLLO DEL GESTO TÉCNICO EN LA BANDAL CHAGUI EN LOS DEPORTISTA DE TAEKWONDO EN LA CATEGORÍA INFANTIL A Y B DE LA LIGA DEPORTIVA CANTONAL DE QUINSALOMA. - GARCIA ZAMBRANO ALAN FABRICIO (2024)
The present research project aims to enhance technical performance in Taekwondo, specifically focusing on Bandal Chagui, targeting young athletes from the Quinsaloma Cantonal Sports League. It centers on the implementation of tailored exercise systems to refine technical skills and their impact on sports performance. The research, of a descriptive and explanatory nature, adopts an empirical and qualitative approach. The overarching and specific objectives revolve around diagnosing, implementing, and evaluating these exercise systems to enhance technical development in Taekwondo. Recommendations are highlighted to integrate these systems into holistic sports training programs and to expand research into other technical movements within the discipline. The methodology employed encompasses a bibliographic, descriptive, and qualitative approach, incorporating a detailed analysis of the problematic situation and justification for the research. The relevance of this study is underscored in the continuous improvement of teaching and training techniques in Taekwondo, contributing to the comprehensive development of athletes. Future research directions are proposed, emphasizing the importance of verifying the authenticity and reliability of consulted sources. Therefore, the document provides a comprehensive and practical perspective for improving technical skills in Taekwondo, with significant implications for both the sports and academic domains, especially within the context of young athletes.